2020
DOI: 10.1590/1807-7692bar2020190149
|View full text |Cite
|
Sign up to set email alerts
|

Local Government Performance: Evaluating Efficiency, Efficacy, and Effectiveness at the Basic Education Level

Abstract: Access to public education for many specialists is the most potent policy toward achieving an equitable and fair society. To accomplish this challenging goal, there must exist an efficient and effective public system. Therefore, to support and expand the issue, we have developed a study that focuses on the impacts that socioeconomic conditions have on efficiency and efficacy at the basic education level in municipalities from the state of São Paulo, Brazil. In order to achieve our main goal, we performed a des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…In Latin America, subnational government performance has been assessed in terms of tax collection Gomes, 2015, Petrovsky andAvellaneda, 2014); financial indicators (Avellaneda 2009b, Gomes et al, 2013; health care scores (Dantas et al, 2017, Olvera and Avellaneda, 2019, Ferraresi, 2021, De Oliveira et al, 2016, Paschoalotto et al, 2018, Ribeiro et al, 2018, Russo et al, 2019, Vargas et al, 2015; electricity and water services, educational achievements (Avellaneda, 2009a, Caetano et al 2017, Queiroz et al, 2020, Rosa et al, 2019, Paschoalotto et al, 2020Santos et al, 2020); and environmental indicators (Dantas et al, 2017, De la Riva 2021.…”
Section: Assessing Municipal Performance and Its Drivers In The Latin...mentioning
confidence: 99%
See 2 more Smart Citations
“…In Latin America, subnational government performance has been assessed in terms of tax collection Gomes, 2015, Petrovsky andAvellaneda, 2014); financial indicators (Avellaneda 2009b, Gomes et al, 2013; health care scores (Dantas et al, 2017, Olvera and Avellaneda, 2019, Ferraresi, 2021, De Oliveira et al, 2016, Paschoalotto et al, 2018, Ribeiro et al, 2018, Russo et al, 2019, Vargas et al, 2015; electricity and water services, educational achievements (Avellaneda, 2009a, Caetano et al 2017, Queiroz et al, 2020, Rosa et al, 2019, Paschoalotto et al, 2020Santos et al, 2020); and environmental indicators (Dantas et al, 2017, De la Riva 2021.…”
Section: Assessing Municipal Performance and Its Drivers In The Latin...mentioning
confidence: 99%
“…Among the contextual drivers, several studies have tested the performance effects of socio-demographic factors (e.g., Avellaneda, 2012;Paschoalotto et al, 2020;Puppim de Oliveira, 2017;Rosa et al, 2019). Some of the existing works suggest that population size, rurality, violence, and population density matter for social service delivery (Avellaneda 2009a, 2009b, Avellaneda and Gomes, 2015, Ferraz et al, 2012, Puppim de Oliveira, 2017, Santos et al, 2020, Zucco, 2013, Queiroz et al, 2020.…”
Section: Assessing Municipal Performance and Its Drivers In The Latin...mentioning
confidence: 99%
See 1 more Smart Citation
“…The performed study had as its object of study the organizational culture of 4 public schools in Brazil, in the State of São Paulo, defined through the polarization of their performance: 02 schools make up part of cluster 01, with high-performance municipalities and 02 schools integrated into cluster 02, with low-performance municipalities. The clusters were created from a sample of 645 municipalities that make up the State of São Paulo and 3 performance indexes: Basic Education Development Index (IDEB) of 2017, IFDMER, FIRJAN Municipal Development Index -Employment and Income (IFDMER) of 2016, and Municipal-Human Development Index (IDHM) of 2010 (Instituto Brasileiro de Geografia e Estat ıstica, 2019; Paschoalotto et al, 2020). Noted here is that the created clusters demonstrated different socio-educational profiles of performance.…”
Section: Data Collection and Research Sitesmentioning
confidence: 99%
“…The performance of subnational governments is relevant to worldwide public administration studies, particularly in understanding these governments' ability to deliver services and improve indicators (Olvera & Avellaneda, 2019;Paschoalotto et al, 2020). Studies such as Bello-Gomez (2020) have observed the influence of subnational governments' performance on health, education, and economic policies.…”
Section: Theoretical Frameworkmentioning
confidence: 99%